Insulin signaling proteins in pancreatic islets of insulin-resistant rats induced by glucocorticoid - de Paula, Flávia M.M; Boschero, Antonio C; Carneiro, Everardo M; Bosqueiro, José R [UNESP]; Rafacho, Alex [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
Chronic administration of glucocorticoids induces insulin resistance that is compensated by an increase in β-cell function and mass. Since insulin signaling is involved in the control of β-cell function and mass, we investigated the content of insulin pathway proteins in pancreatic islets. Rats were made insulin resistant by daily administration of dexamethasone (1mg/kg, b.w., i.p.) for 5 consecutive days (DEX), whilst control rats received saline (CTL). Circulating insulin and insulin released from isolated islets were measured by radioimmunoassay whereas the content of proteins was analyzed by Western blotting. DEX rats were hyperinsulinemic and exhibited augmented insulin secretion in response to glucose (P < 0.01). The IRα-subunit, IRS-1, Shc, AKT, p-p70S6K, ERK1/2, p-ERK1/2, and glucocorticoid receptor protein levels were similar between DEX and CTL islets. However, the IRβ-subunit, p-IRβ-subunit, IRS-2, PI3-K, p-AKT and p70S6K protein contents were increased in DEX islets (P < 0.05). We conclude that IRS-2 may have a major role, among the immediate substrates of the insulin receptor, to link activated receptors to downstream signaling components related to islet function and growth in this insulin-resistant rat model.
Keywords: Dexamethasone; Glucocorticoid; Insulin resistance; Insulin signaling; Pancreatic islets